1996
DOI: 10.2307/1592259
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity Studies of an Arkansas Variant Infectious Bursal Disease Virus

Abstract: A variant infectious bursal disease virus (IBDV), IBDV-s977, was blind passaged in cell culture, plaque purified, and attenuated by serial passage at a high multiplicity of infection (MOI) in chick embryo fibroblasts (CEF). Cell culture passages of virus caused less bursal atrophy and splenomegaly than did the original isolate and retained immunogenicity; however, virus tended to persist for a longer time in the bursa and spleen of birds infected with the highest CEF passages. Antibody to both low MOI and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Results obtained in the present study were similar to those shown by other researchers who reported a decrease in the pathogenicity of IBDV strains propagated in embryos and cell cultures (Müller et al, 1986;Becht & Müller, 1991;Ismail & Saif, 1991;Tsai & Saif, 1992;Tanimura et al, 1995;Bayyari et al, 1996;Hassan & Saif, 1996;Hassan et al, 1996a,b;Takase et al, 1996;Yamaguchi et al, 1996;Chen et al, 1998). However, antigenic and/or immunogenic changes were not recognized in these studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results obtained in the present study were similar to those shown by other researchers who reported a decrease in the pathogenicity of IBDV strains propagated in embryos and cell cultures (Müller et al, 1986;Becht & Müller, 1991;Ismail & Saif, 1991;Tsai & Saif, 1992;Tanimura et al, 1995;Bayyari et al, 1996;Hassan & Saif, 1996;Hassan et al, 1996a,b;Takase et al, 1996;Yamaguchi et al, 1996;Chen et al, 1998). However, antigenic and/or immunogenic changes were not recognized in these studies.…”
Section: Discussionsupporting
confidence: 91%
“…Differences in the relative pathogenicity of IBDV that are apparently related to the host system utilized have been previously reported (Müller et al, 1986;Becht & Müller, 1991;Ismail & Saif, 1991;Tsai & Saif, 1992;Tanimura et al, 1995;Bayyari et al, 1996;Hassan et al, 1996a,b;Hassan & Saif, 1996;Takase et al, 1996;Yamaguchi et al, 1996;Chen et al, 1998;Fussell, 1998). However, these authors did not correlate changes in relative pathogenicity with either antigenic or immunogenic differences.…”
Section: Introductionmentioning
confidence: 79%
“…Pathogenic, antigenic, or immunogenic variation induced by propagation in different host systems has been addressed in other studies (Ismail & Saif, 1991;Tsai & Saif, 1992;Bayyari et al, 1996a; IBDV antigenicity and immunogenicity 467 Hassan & Saif, 1996;Hassan et al, 1996a,b;Yamaguchi et al, 1996). Although these studies documented that changes in the pathogenicity of IBDV occurred following propagation in different host systems, antigenic and/or immunogenic changes were not described.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of host systems on the antigenicity and/or immunogenicity of IBDV is less clear. Tsai & Saif (1992), Bayyari et al (1996a), Hassan et al (1996a,b), Hassan & Saif (1996), and Yamaguchi et al (1996) have indicated that propagation of IBDV in cell culture does not alter its antigenic configuration .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation